Chemical Structure Modification of Polystyrene (PS): A Short Review - A. Mahdi, Suror; Saad Jwad, Rasha; Adnan Hasan, Amer; B. Khudhair, Mohamed; A. Alshareef, Sohad; Ghosh, Sanjay; H. Al-Mashhadani, Mohammed (Al-Nahrain Journal of Science, 2024)
Polystyrene (PS) is a polymer that finds extensive usage in several applications such as electronics, packaging, and healthcare. Its chemical structure may be changed to alter its features and capabilities. This leads to improve the performance of the material to be suitable for specific applications. We discuss the recent PS chemical structure modification in this short review. The review focuses on methods of modification such as functionalization, grafting, and copolymerization. It also investigates the impact of various modification options such as PS’s mechanical strength, photo-stability, and surface features. It also looks at the wide range of approaches in which modified PS materials are used. We talk about the field’s prospects and problems going forward. This is including as improvements in modification methods, incorporating sustainable practices and investigation of new applications. Moreover, it is tackling important scalability, regulatory compliance, and end-of-life issues. By focusing on innovation and resolving future issues, we hope to shed light on the adaptability and potential of modified PS materials through this review.